Smart Phone Apps: An Innovative Approach to Improving Pediatric Medication Adherence - Rebecca M. Wytiaz; Hyung M. Lee; Olufunmilola K. Odukoya (University of Minnesota Libraries Publishing, 2015)
Children suffering from chronic illnesses often struggle to adhere to their medication regimens and are rarely involved in the management of their medications. The use of innovative technology, such as medication adherence mobile apps, may be beneficial in increasing medication adherence rates and self-care knowledge in the pediatric population. Children serve as an optimal population with which to use mobile apps as intervention tools, as children utilize smart phone technology far more than most other populations. By striving to improve children's medication perceptions, adherence and willingness to continue medication therapy for a chronic condition may improve during adolescent years and may persist as they transition into adulthood. As community pharmacists interact with children with chronic conditions during routine visits, they can also engage them in conversations about their medication adherence through use of mobile apps. Although many medication adherence apps are currently available on the market, none of these apps are tailored towards pediatric patients. Thus, further research should be conducted in order to develop mobile apps conducive to this population.   Type: Student Project